The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcvm.2022.926378
|View full text |Cite
|
Sign up to set email alerts
|

Detection of myocardial fibrosis: Where we stand

Abstract: Myocardial fibrosis, resulting from the disturbance of extracellular matrix homeostasis in response to different insults, is a common and important pathological remodeling process that is associated with adverse clinical outcomes, including arrhythmia, heart failure, or even sudden cardiac death. Over the past decades, multiple non-invasive detection methods have been developed. Laboratory biomarkers can aid in both detection and risk stratification by reflecting cellular and even molecular changes in fibrotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 138 publications
(164 reference statements)
0
6
0
Order By: Relevance
“…1a-b). Increase in wellknown pro-fibrotic transcription factors (including RUNX1 25 and MEOX1 26 ) and pro-fibrotic genes (including ACTA2 27 , TAGLN 28 , SMOC2 29 and COL1A1) were also observed in the myocardial tissue from these patients (Supplemental Fig. 1a).…”
Section: Resultsmentioning
confidence: 75%
“…1a-b). Increase in wellknown pro-fibrotic transcription factors (including RUNX1 25 and MEOX1 26 ) and pro-fibrotic genes (including ACTA2 27 , TAGLN 28 , SMOC2 29 and COL1A1) were also observed in the myocardial tissue from these patients (Supplemental Fig. 1a).…”
Section: Resultsmentioning
confidence: 75%
“…Although the LA and LV diameters, volumes, and ejection percentages did not differ substantially between MetS participants with and without DM, the 2D-STE revealed LA and LV deformation features that were significantly worse in the presence of DM, indicating subclinical dysfunction ( p < 0.04). According to previous research, the pattern of myocardial deformation is highly related to the severity of myocardial fibrosis determined by cardiac MRI or histopathologic samples [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…69 Some of them may be useful to characterize myocardial tissue composition (eg, echocardiographic assessment of myocardial reflectivity and deformation, cardiac magnetic resonance [CMR], and computed tomography). 70 In this regard, integrated backscatter is a traditional echocardiographic approach to indirectly detect myocardial fibrosis by quantitative evaluation of ultrasound reflectivity and, more recently, strain parameters derived from the speckle tracking echocardiographic technique have been proposed that reflect the altered myocardial deformation of fibrotic tissues. 70 However, CMR based on native T1 mapping and extracellular volume (ECV) quantification is the current gold standard imaging method to evaluate MIF.…”
Section: Clinical Management Of Mif In Hhd Diagnosis Of Mif In Hhdmentioning
confidence: 99%
“…70 In this regard, integrated backscatter is a traditional echocardiographic approach to indirectly detect myocardial fibrosis by quantitative evaluation of ultrasound reflectivity and, more recently, strain parameters derived from the speckle tracking echocardiographic technique have been proposed that reflect the altered myocardial deformation of fibrotic tissues. 70 However, CMR based on native T1 mapping and extracellular volume (ECV) quantification is the current gold standard imaging method to evaluate MIF. Indeed, several studies have shown direct correlations between the ECV and the quantity of interstitial collagen deposition in cardiac patients with and without HF, 71 although none of these studies included patients with HHD.…”
Section: Clinical Management Of Mif In Hhd Diagnosis Of Mif In Hhdmentioning
confidence: 99%